Risk assessment and molecular mechanism study of drug-drug interactions between rivaroxaban and tyrosine kinase inhibitors mediated by CYP2J2/3A4 and BCRP/P-gp - Tingting Zhao; Xuening Li; Yanwei Chen; Jie Du; Xiaodong Chen; Dalong Wang; Liyan Wang; Shan Zhao; Changyuan Wang; Changyuan Wang; Qiang Meng; Qiang Meng; et al. (Frontiers Media S.A., 2022)
Cancer patients generally has a high risk of thrombotic diseases. However, anticoagulant therapy always aggravates bleeding risks. Rivaroxaban is one of the most widely used direct oral anticoagulants, which is used as anticoagulant treatment or prophylaxis in clinical practice. The present study aimed to systemically estimate the combination safety of rivaroxaban with tyrosine kinase inhibitors (TKIs) based on human cytochrome P450 (CYPs) and efflux transporters and to explore the drug-drug interaction (DDI) mechanisms in vivo and in vitro. In vivo pharmacokinetic experiments and in vitro enzyme incubation assays and bidirectional transport studies were conducted. Imatinib significantly increased the rivaroxaban Cmax value by 90.43% (p < 0.05) and the area under the curve value by 119.96% (p < 0.01) by inhibiting CYP2J2- and CYP3A4-mediated metabolism and breast cancer resistance protein (BCRP)- and P-glycoprotein (P-gp)-mediated efflux transportation in the absorption phase. In contrast, the combination of sunitinib with rivaroxaban reduced the exposure in vivo by 62.32% (p < 0.05) and the Cmax value by 72.56% (p < 0.05). In addition, gefitinib potently inhibited CYP2J2- and CYP3A4-mediated rivaroxaban metabolism with Ki values of 2.99 μΜ and 4.91 μΜ, respectively; however, it almost did not affect the pharmacokinetics of rivaroxaban in vivo. Taken together, clinically significant DDIs were observed in the combinations of rivaroxaban with imatinib and sunitinib. Imatinib increased the bleeding risks of rivaroxaban, while sunitinib had a risk of reducing therapy efficiency. Therefore, more attention should be paid to aviod harmful DDIs in the combinations of rivaroxaban with TKIs.